Sequential and Parallel Algorithms to Compute Turbulent Coherent Structures - Sergio Gandía-Barberá; Andres Cremades; Ricardo Vinuesa; Sergio Hoyas; María Jezabel Pérez-Quiles (Mathematics)
The behavior of turbulent flows remains a significant unsolved problem in physics. Recently, a large quantity of effort has been directed toward understanding the non-linear interactions of the different flow structures in order to address this challenge. In this paper, different implementations of one exact method for identifying these structures are analyzed. This includes two sequential algorithms and a parallelizable one, developed to handle large-scale data efficiently. The new parallel algorithm offers significant advantages in handling the computational demands of large simulations, providing a more scalable solution for future research.